Lip repositioning - Reetika Gaddale; Shrikar R Desai; Jayashree A Mudda; I Karthikeyan (Wolters Kluwer Medknow Publications, 2014)
Excessive gingival display is a frequent finding that can occur because of various intraoral or extraoral etiologies. This report describes the use of surgical lip repositioning technique for the management of a gummy smile associated with vertical maxillary excess and hypermobility of the upper lip. The procedure restricts the muscle pull of the elevator lip muscles by shortening the vestibule, thus reducing the gingival display when smiling. Healing was uneventful and follow-up examinations of 10 months revealed reduced gingival display. For patients desiring a less invasive alternative to orthognathic surgery, lip repositioning is a viable alternative.